2019
DOI: 10.4049/jimmunol.1801400
|View full text |Cite
|
Sign up to set email alerts
|

Bach2 Controls T Follicular Helper Cells by Direct Repression of Bcl-6

Abstract: T follicular helper (Tfh) cells are a specialized T cell subset that regulates the long-lived production of highly specific Abs by B cells during the germinal center (GC) reaction. However, the transcriptional network sustaining the Tfh cell phenotype and function is still incompletely understood. In this study, we identify the transcription factor Bach2 as a central negative regulator of Tfh cells. Ectopic overexpression of Bach2 in murine Tfh cells resulted in a rapid loss of their phenotype and subsequent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…Other studies have confirmed the association between some intronic SNPs and immunemediated diseases including celiac disease, type 1 diabetes, RA, and autoimmune Addison's disease [20,22]. Bach2 is downregulated and low expressed in Tfh cells [25,26]. Bach2 is a crucial negative regulator of Tfh cells to remain its steady state and restrain its pathogenic accumulation [25].…”
Section: The Effect Of Bach2 On Th17mentioning
confidence: 90%
See 2 more Smart Citations
“…Other studies have confirmed the association between some intronic SNPs and immunemediated diseases including celiac disease, type 1 diabetes, RA, and autoimmune Addison's disease [20,22]. Bach2 is downregulated and low expressed in Tfh cells [25,26]. Bach2 is a crucial negative regulator of Tfh cells to remain its steady state and restrain its pathogenic accumulation [25].…”
Section: The Effect Of Bach2 On Th17mentioning
confidence: 90%
“…Bach2 is downregulated and low expressed in Tfh cells [25,26]. Bach2 is a crucial negative regulator of Tfh cells to remain its steady state and restrain its pathogenic accumulation [25]. It critically regulates Tfh cell differentiation.…”
Section: The Effect Of Bach2 On Th17mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FOXO1 is not the only factor affecting Tfh‐cell differentiation in the presence of activated PI3Kδ (Figure ). Recent studies defined a role for the transcription factor BACH2 in antagonizing Tfh‐cell formation through suppression of Bcl6 , directly binding its promoter and displacing a BATF/IRF4 complex, as well as suppressing expression of CXCR5 . BACH2, like FOXO1, is inactivated by phosphorylation by AKT, suggesting lower BACH2 activity in Pik3cd E1020K/+ T cells further promotes a Tfh‐cell program.…”
Section: Pi3k Signaling Pathways Orchestrating T Follicular Helper Cellsmentioning
confidence: 99%
“…BACH2 represses both Prdm 1 and Bcl6 and its inactivation promotes the generation of multiple effector cell lineages and decreases Treg formation (Figure ). Indeed, Tfh cells express only low levels of BACH2, suggesting that balanced activity of this transcriptional repressor facilitates distinct types of T‐helper–cell development. Finally, phosphorylation of the histone methyltransferase EZH2 by AKT inhibits EZH2‐mediated promotion of memory cell and drives effector cell generation …”
Section: T‐helper–cell Differentiationmentioning
confidence: 99%